2015
DOI: 10.3945/ajcn.114.106096
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin and carotenoid intake and risk of head-neck cancer subtypes in the Netherlands Cohort Study

Abstract: With this study, we show an inverse association between intake of vitamin C and the incidence of HNC and HNC-subtypes. Future research is recommended to investigate the underlying mechanisms and to confirm our results, which may be promising for the prevention of HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
1
24
0
2
Order By: Relevance
“…Moreover, a meta-analyses based on 15 case-control and one cohort studies revealed a protective role of fruit and vegetables consumption 49 . In the Netherlands Cohort Study, an inverse association was observed between intake of nutrients like vitamin C and food items like fruits and vegetables; and the incidence of head and neck cancers including oral cancers 50, 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a meta-analyses based on 15 case-control and one cohort studies revealed a protective role of fruit and vegetables consumption 49 . In the Netherlands Cohort Study, an inverse association was observed between intake of nutrients like vitamin C and food items like fruits and vegetables; and the incidence of head and neck cancers including oral cancers 50, 51 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have been conducted to examine various other dietary components, patterns and indices in relation to oral and pharyngeal cancer. [44][45][46][47][48][49][50] In the pooled analyses within the International Head and Neck Cancer Epidemiology Consortium folate, 46 vitamin C, 44 coffee and tea intake 47 were found to be protective against oral and pharyngeal cancer. Moreover, a meta-analyses based on 15 case-control studies and one cohort study revealed a protective role of fruit and vegetables consumption.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Recent meta-analyses have shown an inverse correlation between ascorbate intake and risk of head and neck42,43 and gastric cancer,44 and there is substantial public interest in dietary ascorbate as a cancer-preventive agent 45. In our study, the 330 mg/L dose produced plasma ascorbate levels halfway between saturation and deficiency, which is similar to levels in human populations,46 with mean ascorbate plasma levels in the general population being 40–50 μM, substantially below human saturation levels of ~80 μM 46,47.…”
Section: Discussionmentioning
confidence: 99%
“…Overall number of preclinical and observational research studies regarding the role of lutein and zeaxanthin in prevention or reducing the intensity of different cancers continues to evolve from basic research as well as from human studies. These studies directed to bioavailability, metabolism, and dose-response relationships with intermediary biomarkers and clinical outcomes to determine and verify the role of lutein and zeaxanthin in controlling tumor growth in humans (Bertone et al, 2001;Boeke et al, 2014;Chew & Park, 2004;Cho et al, 2003;de Munter, Maasland, van Nkondjock & Ghadirian, 2004;Silvera, Jain, Howe, Miller, & Rohan, 2006;Wang et al, 2014;Yuan, Stam, Arakawa, Lee, & Yu, 2003;Zhang et al, 1999). Although scientific evidence in support of the beneficial role of egg yolk carotenoids in prevention or reducing the intensity of AMD and CVD and neurodegeneration are substantial, research findings about the role of egg carotenoids on different cancers are inconclusive or inconsistent and warranted further research studies, meta-analyzes, to confirm the advantageous effect of egg carotenoids.…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%